2013
DOI: 10.1080/15226514.2012.683209
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Translocation of Ti From Nanoparticles in Crops and Wetland Plants

Abstract: Bioavailability of engineered metal nanoparticles affects uptake in plants, impacts on ecosystems, and phytoremediation. We studied uptake and translocation of Ti in plants when the main source of this metal was TiO2 nanoparticles. Two crops (Phaseolus vulgaris (bean) and Triticum aestivum (wheat)), a wetland species (Rumex crispus, curly dock), and the floating aquatic plant (Elodea canadensis, Canadian waterweed), were grown in nutrient solutions with TiO2 nanoparticles (0, 6, 18 mmol Ti L(-1) for P. vulgari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(54 citation statements)
references
References 34 publications
1
47
0
2
Order By: Relevance
“…Scattered accumulations of titanium tetragonal and cylindrical crystals were found in various samples under TEM ( Figure 4D ; compared with Figure 4C ). Previous studies on Phaseolus vulgaris , Triticum aestivum , and Rumex crispus have also demonstrated the transport of TiO 2 NPs across plant tissues (Jacob et al, 2013). Xia et al (2015) reported the internalization of TiO 2 NPs into marine alga, N. closterium through TEM and cytometry.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Scattered accumulations of titanium tetragonal and cylindrical crystals were found in various samples under TEM ( Figure 4D ; compared with Figure 4C ). Previous studies on Phaseolus vulgaris , Triticum aestivum , and Rumex crispus have also demonstrated the transport of TiO 2 NPs across plant tissues (Jacob et al, 2013). Xia et al (2015) reported the internalization of TiO 2 NPs into marine alga, N. closterium through TEM and cytometry.…”
Section: Resultsmentioning
confidence: 94%
“…Thus, TiO 2 NPs induced P and Mg uptake and further supported our photosynthetic observations. The increase of S content in response to TiO 2 NPs is understandable as it is the principle amino acid of GSH meant for detoxification of metals and xenobiotic (Jacob et al, 2013). Contrary to these elements, Fe content significantly decreased in root as well as leaves under TiO 2 NPs exposure ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The role of nodes for NP uptake remains to be elucidated. Comparative studies of NP uptake or effects in plants with/without nodes usually report less or absent NP transport/effects in the latter (Jacob et al, 2013;Pokhrel & Dubey, 2013;Schwabe et al, 2013).…”
Section: Nodesmentioning
confidence: 99%
“…For example, treatment of cucumber with 500 mg/L of TiO 2 NPs increased the potassium content by 35 % and phosphorous content by 34 % in cucumber seedlings. Jacob et al (2013) also reported that plant uptake of micronutrients such as Mn and Mg in nutrient solution coexisted with TiO 2 NPs was altered due to the presence of TiO 2 NPs.…”
Section: Engineered Nanomaterials Mitigated Uptake Of Environmental Cmentioning
confidence: 95%
“…Both crystal phases of TiO 2 NPs (anatase and rutile) were taken up by wheat, and they maintained their phase structure in plant tissues. Jacob et al (2013) reported that exposure of wheat and beans to nutrient solution containing TiO 2 NPs as a single source of Ti significantly increased root Ti sorption and uptake. However, upward translocation was not reported for these two crops.…”
Section: Uptake and Accumulation Of Titanium Dioxidementioning
confidence: 98%